Digital Transformation and the Need for Non-Formal Education Curriculum: An Analytical Study of PKBM and SKB - Fatmawati Intang; Syamsiarna Nappu (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The purpose of this research is to analyze the needs of a non-formal education curriculum based on digital transformation in PKBM and SKB in Wajo Regency. The research uses a qualitative descriptive approach with a needs analysis design. Data sources include PKBM/SKB managers, tutors, students, elements of the Education Office, and institutional documents. Data was collected through interviews, observations, documentation studies, and needs questionnaires, then analyzed through data reduction, data presentation, triangulation, and conclusion drawn. The results of the study show that the main needs include strengthening students' digital literacy, improving tutor digital competence, developing flexible learning, digital management, infrastructure, varied assessments, and local potential-based skills programs. The contribution of this research lies in the formulation of the basis for the development of a non-formal education curriculum that is not only oriented towards diplomas, but also the empowerment, life skills, job skills, and digital readiness of learning citizens.